Knowledge, attitudes, and practices of Native Americans in northern California regarding ticks and tick-borne diseases - Patricia Torres; Elizabeth F. Pienaar; Michelle A. Ritchie; Mourad W. Gabriel; Michael J. Yabsley (One Health)
Reports of tick-borne diseases (TBDs) are increasing worldwide, particularly in North America where a diversity of endemic and exotic tick species and pathogens occur. Native American populations have unique outdoor cultural and occupational practices that may impact their exposure to ticks, yet this risk remains understudied in the context of TBD. To address this gap, we examined knowledge, attitudes, and practices regarding ticks and TBDs among Native American communities in Humboldt County, California. We conducted semi-structured interviews with participants, who represented various tribes, at a cultural gathering. Cultural practices intertwined closely with outdoor activities (e.g., ceremonies, dances), potentially influencing local tick exposure patterns. Most research participants had been bitten by ticks and reported tick exposure by children and pets. Research participants demonstrated low knowledge about ticks and TBDs, as well as low levels of risk perceptions pertaining to TBDs. Research participants most commonly conducted tick checks after outdoor activity, wore long-sleeved clothing outdoors, and used homeopathic remedies or essential oils to prevent exposure to ticks and TBDs. Culturally appropriate outreach and education initiatives are needed to address TBD risk among Native American communities. Our study lays the groundwork for future research on the intersection of cultural practices and tick exposure, with implications for public health interventions that are tailored to the needs of indigenous populations.